The Factors Influencing Revisit Intention: A Study of Tourism in Malang, Indonesia - Unarto, Tirto; Narasuci, Win; Budiarti, Lina; Wijayanti, Rena Feri; Evelina, Tri Yulistyawati (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the influencing of revisit intention in Malang. This research was conducted in April-July 2025. This study uses a quantitative approach with the sampling technique in this study using purposive sampling, data collected by questionnaire using Google Form with a sample of 221 respondents who were analyzed using with SPSS 27 for a descriptive analysis and using structural equation modelling with AMOS 23. The results of this study indicate that five hypotheses were accepted, while one hypothesis was rejected. Destination image has a significant effect on tourist satisfaction, electronic word of mouth also has a significant effect on destination image and it has a significant effect on destination trust. Furthermore, tourism satisfaction has a significant effect on destination trust, and destination trust has a significant effect on revisit intention. Meanwhile, tourism satisfaction does not have a significant effect on revisit intention.